Cuba’s convertible currency debt problem - A.R.M. Ritter (CEPAL Review, 1988)
In the decade of the 1980s, Cuba has confronted a worsening debt problem in terms of convertible currency and in the context of its participation in the world economy. Before 1985, the debt problem appeared to be manageable, indeed it did not seem to be seriously damaging to Cuba’s macroeconomic growth performance, which was strong from 1981 to 1985 in contrast to most other developing country debtors, which underwent profound economic contraction in this period.